1999
DOI: 10.1007/s005350050215
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid turnover in the inflamed intestinal mucosa: Arachidonic acid-rich phosphatidyl/plasmenyl-ethanolamine in the mucosa in inflammatory bowel disease

Abstract: Cytosolic phospholipase A2 (PLase A2) is activated by low Ca2+ concentrations and translocates from the cytosol to the cell membrane, releasing arachidonic acid; the arachidonic acid cascade then leads to the production of many inflammatory mediators. The aim of this study, accordingly, was to investigate the role of phospholipid metabolism in the intestinal mucosa in inflammatory bowel disease (IBD). Surgically resected specimens from patients with Crohn's disease (CD), ulcerative colitis (UC), and colrectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…In a first exploration, we performed a comparison between representative reference genomes for each of these species, generating a view of the differential KEGG pathways (Figure 3). The species increased in CD uniquely contributed pathway components of glycerophospholipid and lipopolysaccharide metabolism, found to instigate inflammation (Morita et al, 1999), and phosphonoacetate hydrolase, providing access to a novel carbon and phosphate source not accessible to most other organisms (Kim et al, 2011). Interestingly, the latter is a zinc-dependent enzyme that might contribute to a mineral deficiency common in newly diagnosed IBD patients.…”
Section: Resultsmentioning
confidence: 99%
“…In a first exploration, we performed a comparison between representative reference genomes for each of these species, generating a view of the differential KEGG pathways (Figure 3). The species increased in CD uniquely contributed pathway components of glycerophospholipid and lipopolysaccharide metabolism, found to instigate inflammation (Morita et al, 1999), and phosphonoacetate hydrolase, providing access to a novel carbon and phosphate source not accessible to most other organisms (Kim et al, 2011). Interestingly, the latter is a zinc-dependent enzyme that might contribute to a mineral deficiency common in newly diagnosed IBD patients.…”
Section: Resultsmentioning
confidence: 99%
“…22 This may be related to alterations in phospholipid turnover that has previously been associated with the inflamed mucosa of IBD patients. 23 The importance of bacterial xenobiotics metabolism in the gut was first highlighted when it was found that xenobiotics exposure induced expression of bacterial genes involved in drug resistance and metabolism. In a more recent study of mouse model colitis, xenobiotics metabolism pathways, particularly benzoate biodegradation, were implicated to promote the growth of Enterobacteriaceae, a family of bacteria enriched during colitis.…”
Section: Discussionmentioning
confidence: 99%
“…To support the hypothesis that a preferential ω-6 LCFA metabolism occurs in the intestine, increased phospholipid turnover and elevated levels of phospholipase A 2 have been reported in both UC and CD mucosal biopsies, 38 which results in an increase in AA hydrolysis and the downstream generation of proinflammatory oxidized AA lipid mediators. For example, elevations in LTB 4 , as well as the enzymes necessary for its production, have been detected in colonic biopsies of IBD patients.…”
Section: Lipid Metabolism In Ibdmentioning
confidence: 94%